Fundamental thermodynamics of ideal absorption cycles - Tozer, R.M.; James, R.W.
Starting from the representation of a real absorption refrigeration cycle on a temperature-entropy diagram, step-by-step idealisations of the binary mixture, together with the thermodynamic transformations are considered, in order to derive the ideal thermodynamic absorption cycle performance and temperature formulae. It is emonstrated that the ideal absorption cycle is the combination of a Carnot driving cycle with a reverse Carnot cooling cycle. The resorption cycle is analysed in the same manner. Information is included on absorption cooling with heat recovery cycles, heat pumps and temperature amplifiers. From the analysis of single-stage cycles, and by superimposing absorption cycles operating at different temperatures and utilising specific residual heat of the higher temperature sub-cycles, the performance and temperature relations of double, triple and multistage cycles are derived. Special attention is given to three types of triple-stage cycle and their ideal equivalence is demonstrated and represented on the pressure-temperature-concentration (PTX)diagram. A simple hybrid absorption-compression cycle is analysed and the results are compared with those of ideal cold generation cycles (combinations of driving and cooling cycles). Consideration is also given to cold generation systems. Finally, the validation of the fundamental thermodynamics of absorption cycles is presented by applying an exergy analysis. This paper presents the thermodynamic principles involved to obtain simple formulae, in a similar way to the Carnot cycle in order to convey the ideal theoretical limitations.
Keywords: ABSORPTION; REFRIGERATION; RESORPTION; HEAT RECOVERY; HEAT PUMP; TEMPERATURE AMPLIFIER; IDEAL CYCLES; THERMODYNAMICS; MULTISTAGE; EXERGY; COGENERATION